Local food diversification in the Free Nutritious Meal Program: A development communication and SDGs perspective - Rona Agustin; Dhiyaa Thurfah Ilaa; Dhiya Alfiyyah Ansar (Priviet Social Sciences Journal, 2026)
Indonesia possesses abundant food biodiversity; however, its national food system remains highly dependent on rice and imported wheat-based products, limiting food diversification and increasing its vulnerability to global crises and climate change. The Free Nutritious Meal Program has emerged as a strategic policy to improve nutritional outcomes and promote the utilization of local food resources. This study aimed to analyze local food diversification within the Free Nutritious Meal Program from the perspectives of development communication and Sustainable Development Goals (SDGs). This study employed a descriptive qualitative approach using a literature review. Data were collected from scientific journals, government policy documents, official reports, and relevant publications published between 2015 and 2025. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings indicate that the success of local food diversification depends not only on food production and distribution systems but also on policy communication, media framing, nutritional education, community participation, and institutional support. The program has significant potential to contribute to SDG 2 (Zero Hunger), SDG 3 (Good Health and Well-Being), SDG 12 (Responsible Consumption and Production), and SDG 15 (Life on Land). This study contributes to the literature by integrating local food diversification, development communication, the Free Nutritious Meal Program, and SDGs perspectives into a single analytical framework. This study highlights the importance of participatory and sustainable communication strategies in transforming local food into a competitive and sustainable national food identity.